SOCIO-DEMOGRAPHIC AND CLINICAL PROFILE OF HIV POSITIVE PATIENTS ATTENDING INTEGRATED COUNSELING & TESTING CENTRE OF A PRIMARY HEALTH CENTRE IN DELHI (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: The Human Immunodeficiency Virus (HIV) infection is a global pandemic affecting principally the sexually active and economically productive population of any country. Additionally the dual epidemic of HIV and TB infection is of growing concern in Asia, where nearly two-third of TB-infected individuals live and where tuberculosis now accounts for 40 percent of HIV/AIDS deaths. Keeping this in mind, a study was conducted to understand the profile of HIV/AIDS patients attending Integrated Counseling and Testing Center (ICTC) located at Primary Health Centre, Palam in Delhi.Methodology: This was a descriptive record based study undertaken at ICTC, PHC PALAM, New Delhi. Records of all HIV seropositive patients identified in reference period (January 2010 to December 2014) were analyzed retrospectively to assess the socio-demographic and clinical profile including possible route of transmission, CD4 counts at the time of first reporting to the Anti Retroviral Treatment (ART) centre and the presence of co-infections including tuberculosis were recorded. Total 77 HIV seropositive patients were identified.Results: Mean Age of presentation of male was 31.18 ± 8.85 years (12-60 years) and female 30.30 ± 10.07 years (7-53 years). Majority of HIV+ persons were married (16% of males and 6% females were unmarried).24% of women were widows. Majority of HIV+ males and females had only primary schooling. 11% males and 21% females were illiterate. Main occupations of HIV+ males were daily wages labor and salaried service or other unspecified four out of 5 HIV+ women were housewives 70% of subjects were either referred from RNTCP or were self reporting. Heterosexual route was the most common route of transmission. Mean CD4 counts Males: 190.48 ± 180.52, Females: 286.21 ± 220.25 (t=2.09; p=0.039, significant).At the time of first reporting to ART centers, mean CD4 count was significantly higher in HIV+ females as compared to males. More than 50% of HIV+ males and 30% of females had co-infection of HIV & TB. CD4 count was associated with gender and co-infection with TB. Significantly higher odds of HIV-TB co-infection among male as compared to females (chi-square=4.49, p=0.034) and odds Ratio=2.76(1.07 – 7.14)Conclusions: Low literacy and some occupations carry higher risk of HIV. CD4 count was associated with gender and co-infection with TB. Odds of co-infection with TB were higher in males. Analysis of information at ICTC & ART centre should be used to monitor and plan HIV prevention and control in the area.SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), page: 22-26